Detection of simultaneous mechanical faults in 6‐kV pumping induction motors using combined MCSA and stray flux methods. Issue 5 (10th March 2021) - Gyftakis, Konstantinos N.; Panagiotou, Panagiotis A.; Spyrakis, Dimitrios
Abstract: The popularity of stray and air‐gap flux monitoring methods is increasing. This trend is justified by several advantages of such methods over the stator current monitoring that has been demonstrated for electrical fault detection in the induction and synchronous machines. However, the use of the magnetic flux for mechanical faults detections has not drawn this much attention, while in industry, the vibration analysis continues to be popular. This study comes to bridge this gap via the detection of mechanical faults of 6‐kV induction motors in a pumping station. The diagnostic procedure mainly involves the stator current and stray flux monitoring, and harmonic index analysis. The localisation of the fault has been made possible via oscillometer readings. It will be shown that mechanical faults have a very different impact on the stator current and the flux signals, while the flux is not sensitive to the bearing fault mechanisms.